Understanding interactive network branding in SME firms - Koporcic, Nikolina; Törnroos, Jan-Åke (Emerald Publishing Limited, 2019)
Introducing the innovative concept of Interactive Network Branding (INB), this book offers academics and professionals a theoretical framework, alongside practical examples, to develop INB in the context of small and medium-sized enterprises (SMEs). Combining a business network approach with contemporary corporate branding research, a variety of topics are explored, including: strategizing in SME networks, market management, corporate identity, corporate reputation, human-to-human (H2H) interactions. This broad range of perspectives, from business networks to corporate branding, highlights the latest trends in both business marketing and organizational research whilst emphasizing the influential role of human actors in SMEs. Looking at successful cases of INB and analysing cases where branding has gone wrong, Understanding Interactive Network Branding in SME Firms offers guidelines for researchers in marketing theory and practitioners working in SME firms to develop their branding models and processes in fast changing business environments.